Intelligent Systems Technologies and Applications Volume 1 - Berretti, Stefano; Thampi, Sabu M.; Srivastava, Praveen Ranjan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book contains a selection of refereed and revised papers of Intelligent Techniques and Applications track, and the Special Track on Intelligent Image Processing and Artificial Vision track originally presented at the International Symposium on Intelligent Systems Technologies and Applications (ISTA), August 10-13, 2015, Kochi, India.  .
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence